Patient preferences in hidradenitis suppurativa (APProach-HS): a discrete choice experiment - Faverio, Kristin; Ludwig-Peitsch, Wiebke; Görig, Tatiana; Schneider-Burrus, Sylke; Benzel, Friderike; Goebeler, Matthias; Schummer, Patrick; Badran, Alaa; Schaarschmidt, Marthe-Lisa; Harth, Wolfgang; Mößner, Rotraut; Kromer, Christian (Journal der Deutschen Dermatologischen Gesellschaft, 2022)
Background and Objectives: Treatment options for moderate-to-severe hidradenitis suppurativa (HS) comprise antibiotics, biologics, and different surgical methods. These approaches differ substantially regarding the treatment process, success rates, and adverse events. However, information on patient preferences for HS therapies is hitherto scarce. Our aim was to assess patient preferences for medicamentous and surgical treatment of HS with conjoint analysis. Patients and Methods: In this cross-section study, computerized discrete choice experiments were used to quantify patient preferences for HS therapies decomposed into treatment modality (tablets, subcutaneous injections, surgery with secondary-intention healing or primary closure), probability of sustained therapeutic success, probability of mild or severe adverse events, and duration of treatment or wound healing. Results: Averaged over the cohort (n = 216 patients with HS), sustained therapeutic success was considered as most important (Relative Importance Score [RIS]: 36.2), followed by the treatment modality (RIS: 24.0), and duration of treatment/wound healing (RIS: 19.9), whereas mild or severe adverse events (RIS: 10.7 or 9.3) were regarded as less relevant. Patients preferred tablets, followed by subcutaneous injections, and disliked surgery with primary closure. Preferences differed significantly dependent on age and affected body regions. Conclusions: Awareness of patient preferences is essential for patient-centered care in HS.
Gesehen am 10.07.2023